Implementasi Metode EOQ (Economic Order Quantity) Pada Toko Fashion Muna - Fatimah, Ega; Deviagisti, Natasha Cecilia; Nurjaya, Rahma; Priadinata, Stefanus; Suherman, Ujang (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Effective inventory management helps companies meet customer demand in a timely manner, prevent shortages that can disrupt the supply chain, and minimize excessive storage costs. The use of the Economic Order Quantity (EOQ) method is very important to understand the urgency of this method in the context of trading companies, especially children's fashion at Muna fashion stores. The correct strategy for developing a business means that a business still requires many methods to achieve success. In this article we will discuss EOQ squeeze in the Muna fashion shop business.